ASEAN's half century a political history of the Association of Southeast Asian Nations - Weatherbee, Donald E. (Lanham Rowman & Littlefield, 2019)
"Offers a critical analysis of the conventional wisdom regarding ASEAN and its efforts to transform Southeast Asia's security environment"--
Introduction to ASEAN : ASEAN's fiftieth birthday -- The founding of ASEAN : the Bangkok Declaration -- ASEAN's first reinvention : the 1976 First ASEAN Summit -- The Third Indochina War : the situation in Kampuchea -- The expansion of ASEAN : from five to ten -- Adapting to peace : the 1988 Third ASEAN Summit -- ASEAN's second reinvention : the 1992 Fourth ASEAN Summit -- ASEAN's third reinvention : the building blocks of the ASEAN community -- Intra-ASEAN conflict : norms vs. behavior -- ASEAN's existential crisis : the South China Sea conflicts -- ASEAN's vision 2025 : a fourth reinvention?.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: ASEAN -- History; Security, International -- Southeast Asia; Southeast Asia -- Foreign relations; Southeast Asia -- Politics and government -- 1945-.